Corporate performance under corporate governance in the GCC countries / Wael E. AL-Rashed - AL-Rashed, Wael E. (Universiti Teknologi MARA Cawangan Selangor, 2010)
This study is an attempt to explore the relation between the new corporate governance enforcement in the Gulf -GCC- countries and management performance at large. Independent variables within corporate governance cluster have been identified to determine their possible effect on other dependent variables within the cluster of management performance. The study provides empirical support of the added value of corporate governance at both the national as well as the regional level. A deductive research method is adopted to better identify the problem and reach some conclusions. It includes a recognized statistical testing as well as a basic arithmetic model to build up some relationships which may lead to some sort of correlations that assist in interpreting and determining perceptions toward the issue. Results have shown noticeable impact of the same across the tested data and calls for more rigid enforcement of legislative governance among GCC firms.